PILLARIZATION OF LAYERED TETRATITANATES ANION BY ZIRCONIUM(IV) POLYCATION SPECIES - Hari Sutrisno; Endang Dwi Siswani (Universitas Gadjah Mada, 2009)
Pillaring layered tetratitanates anion by zirkonium(IV) polycation species has been realized by three steps: 1). cation-exchange of potasium tetratitanates, 2). intercalation of n-butylamine compound in layered hydrogen tetratitanates and 3). intercalation of zirconium(IV) polycation species by mixing butylamine-intercalated tetratitanates with an aqueous solution of ZrOCl2.8H2O at pH various: 0.1, 0.9 and 1.8. The procedure was carried out by Chimie Douce method. The structures of titanates and the products which had undergone H+ exchange and intercalated by n-butylamine and zirkonium(IV) polycation spesies were investigated by X-rays Diffractometer (XRD) and X-rays Fluorescence (XRF). It was found in the research that [Zr(H2O)8]4+, [Zr(OH)(H2O)7]3+ or [Zr(OH)2(H2O)6]2+ types have presented in the interlayer of the products. At pH = 0.1 and 0.9, [Zr(OH)(H2O)7]3+ type was pillared more dominated in layered tetratitanates than [Zr(H2O)8]4+ type. At pH 1.8, it was signaled that [Zr(OH)(H2O)7]3+ and [Zr(OH)2(H2O)6]2+ types intercalated in layered tetratitanates.